Contributing Factors to Late Age Pregnancy and its Outcome Among Elderly Primigravidas in Kakamega County,Kenya - Ambetsa, Millicent; wakhungu, jacob; mutai, charles; omoni, grace (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
Delayed childbearing is becoming apparent in developing countries especially among the upper and middle class women as they become increasingly empowered. The objective of this study was to determine the pre-disposing factors to late age pregnancy among childbearing women. A cross sectional survey of childbearing women aged between 18 and 40 years and hospital personnel, in 3 selected hospitals and tertiary institutions in Kakamega County, Kenya was carried out. Purposive and stratified sampling strategies were employed. The findings revealed that although the majority age of primigravidas lies between 26 to 30 years, an increasing number of women at the age of 31 to 40 years were still having their first borns. Primigravidas at such ages were found to be more vulnerable to birth complications. It emerged that prolonged education, financial stability, career development, lifestyle, drug and substance abuse and lack of awareness were the leading contributing factors to delayed pregnancy among child bearing women.